6.3k views
5 votes
Amin is attempting to solve the following equation. (x+1)(x+4)=(x-2)(x-3) solve the equation

User EdwardH
by
5.9k points

2 Answers

4 votes

Explanation:

Hey there!

Given;

(X+1) (X+4) = (x-2) (x-3)

Multiply (X+1) and (X+4) on left side and (x-2) and (x-3) on right side.


{x}^(2) + 4x + x + 4 = {x}^(2) - 3x - 2x + 6

Simplify it.


5x + 4 = - 5x + 6


10x = 6 -4


x = (2)/(10)

Therefore, x= 1/5.

Hope it helps....

User Mark Manickaraj
by
6.0k points
3 votes

Answer: x = 1/5

After expanding, (x+1)(x+4) = (x-2)(x-3) becomes x² + 5x + 4 = x² - 5x + 6. Subtracting x² and adding 5x to both sides, we have 10x = 2 and x = 1/5. You can plug this in to check.

i hope this was helpful! :D

User Areuexperienced
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.